To civil servants under contract - Laegreid, Per (2000)
This article focuses on the introduction of the new top civil servant contract system in New Zealand and Norway. Even though both countries introduced contractual arrangements at the same time, the content of the reforms and their scope, scale and intensity are very different. The New Zealand reform was more radical and internally consistent. In contrast to an aggressive and thorough implementation in New Zealand, the contract system was implemented more cautiously and reluctantly in Norway. The effects of the reform are ambiguous and uncertain in both countries. A transformative perspective focusing on the interconnection between international administrative doctrines, national political-administrative culture, and polity feature is used to understand why contracts reforms have different contents, effects and implications. - Reproduced
Keywords: Civil service - Norway; Civil service - Newzealand; Civil service